Immune Infiltration of Ulcerative Colitis and Detection of the m6A Subtype. (25th June 2022) - Gu, Chenzheng; Wu, Junlu; Zhang, Wei; Yao, Yiwen; Yan, Wenhui; Yuan, Yi; Wang, Weiwei; Shang, Anquan
Abstract : Ulcerative colitis (UC) is an inflammatory bowel disease characterized by persistent colon inflammation. N6-methyladenosine (m6A) methylation is one of the most prevalent RNA modifications with key roles in both normal and illness, but m6A methylation in ulcerative colitis is unknown. This research investigated m6A methylation in UC. We examined the expression of known m6A RNA methylation regulators in UC using the Gene Expression Omnibus database (GEO database). First, we used m6A regulators to examine m6A change in UC samples. These two patient groups were created by clustering three m6A gene expression datasets. These genes were then utilized to build an m6A gene network using WGCNA and PPI. These networks were built using differentially expressed genes. The 12 m6A regulators were found to be dispersed throughout the chromosome. The study's data were then connected, revealing positive or negative relationships between genes or signaling pathways. Then, PCA of the 12 m6A-regulated genes indicated that the two patient groups could be discriminated in both PC1 and PC2 dimensions. The ssGSEA algorithm found that immune invading cells could be easily distinguished across diverse patient groups. Both groups had varied levels of popular cytokines. The differential gene analysis of the two samples yielded 517 genes like FTO and RFX7. It found 9 hub genes among 121 genes in the blue module, compared their expression in two groups of samples, and found that the differences in expression of these 9 genes were highly significant. The identification of 9 possible m6A methylation-dependent gene regulatory networks suggests that m6A methylation is involved in UC pathogenesis. Nine candidate genes have been identified as possible markers for assessing UC severity and developing innovative UC targeted therapeutic approaches.